2001
DOI: 10.1046/j.1464-410x.2001.02305.x
|View full text |Cite
|
Sign up to set email alerts
|

Mercurochrome as an adjunct to local preoperative preparation in children undergoing hypospadias repair

Abstract: Objective To determine whether the local application of mercurochrome over genital skin before surgery, in addition to soap/water scrubs, can help to decrease the incidence of infection patients undergoing hypospadias repair, and thereby the incidence of ®stula formation. Patients and methods The study comprised 44 consecutive boys undergoing primary or repeat surgery for hypospadias between October 1999 and April 2000. They were arbitrarily divided into two groups; group 1 received a conventional local scrub … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…[24] Atraumatic handling of tissue, using skin hooks or stay sutures, rather than forceps is of help. If diversion is indicated, suprapubic tubes are better than intubated perineal urethrostomies.…”
Section: Complicationsmentioning
confidence: 99%
“…[24] Atraumatic handling of tissue, using skin hooks or stay sutures, rather than forceps is of help. If diversion is indicated, suprapubic tubes are better than intubated perineal urethrostomies.…”
Section: Complicationsmentioning
confidence: 99%
“…They reported 57% pathogen microorganisms in local skin swabs before the operation but did not mention whether the local area was the penile shaft or the dorsal or ventral sides of the penis or prepuce. They found that applying preoperative mercurochrome leads to a decrease in the incidence of fistula formation, although it was not statistically significant 12 . It is reported that 56% of local infection on admission and before the operation decreased to 23.3% after preoperative local scrubbing.…”
Section: Discussionmentioning
confidence: 96%
“…Despite pre-operative prepping with povidone-iodine soap/solution, use of prophylactic antibiotics, and/or use of intra-operative antibiotics to prevent SSIs,[ 6 ] minor and moderate SSIs after hypospadias surgery are common enough to be problematic and if severe can cause disruption of repair and wound dehiscence. [ 1 ] In such situations, proximal urinary diversion may even be needed.…”
Section: Discussionmentioning
confidence: 99%